2011
DOI: 10.3151/jact.9.159
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Reinforcing Steel in Fiber Reinforced Cementitious Composites

Abstract: For the purpose of global sustainability the long life of structures is essential and the durability performance of reinforced concrete structures is one of the key issues to be resolved. This paper reports the results of a series of long term corrosion tests on fiber reinforced cementitious composites containing polyethylene (PE) alone and hybrid steel cord (SC) and PE fibers. The results are also compared with ordinary mortar. The specimens are subjected to accelerated corrosion for one year by applying exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 12 publications
1
44
0
Order By: Relevance
“…Based on the above, the performance of a structure has been confirmed to improve through the use of HPFRCC as the construction material, and this material is expected to be used widely in the future. However, there has been little research on the durability of HPFRCC particularly against attacks from chloride and carbonation (Sanjuan et al 1997;Lawler et al 2002;Maalej et al 2003;Martinola et al 2004;Mihashi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above, the performance of a structure has been confirmed to improve through the use of HPFRCC as the construction material, and this material is expected to be used widely in the future. However, there has been little research on the durability of HPFRCC particularly against attacks from chloride and carbonation (Sanjuan et al 1997;Lawler et al 2002;Maalej et al 2003;Martinola et al 2004;Mihashi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the crack-bridging capacity of the fiber in specimens that are placed in a marine-like environment is increased by corrosion. Sadeghi-Pouya et al and Mihashi et al [12,13] investigated that steel fibers in cylinder specimens show less damage than the normal bar in these samples. Moreover, the Flexural performance of specimens with corroded steel fiber is not decreased by corrosion attack.…”
Section: Comparison Of Steel Bar and Steel Fiber Corrosionmentioning
confidence: 99%
“…Thus, steel fiber will be corroded before the steel bar and the corrosion of steel bar will be reduced or stopped. The rest of the steel fibers that is disconnected to the steel bar will be preserved by the concrete alkalinity [13]. Therefore, in pre-cracked (R+S)C beams, bonding between bar and cement past will be higher than the pre-cracked RC beams.…”
Section: Flexural Strength and Toughness Of Pre-cracked Beams In Marimentioning
confidence: 99%
“…Sanjuan et al (1997) reported that FRCC containing only 0.5 vol.% of polypropylene with W/C=0.5 demonstrated an ability for self-healing of cracks under a corrosive environment. Mihashi et al (2011) reported the results of a series of long-term corrosion tests on FRCC containing PE alone and hybrid fiber (i.e. mix of steel cord and polyethylene: SC+PE).…”
Section: Engineering With Fiber Reinforcementmentioning
confidence: 99%
“…The recovery in deflection capacity and stiffness was found to range between 65% and 105% in virgin specimens, significantly higher compared to the specimens without benefit of the self-healing process. Mihashi et al (2011) declared FRCC to have better resistance against corrosion of steel bars than mortar because of the fiber bridging of cracks and the self-healing of some of the cracks. fibers achieves more effective self-healing.…”
Section: Introductionmentioning
confidence: 99%